Bmp5 Mutation Alters circRNA Expression During Embryonic External Ear Development. Issue 6 (29th September 2022) - Liu, Wei; Lin, Lin; Wang, Qiushi; Yang, Qinghua; Jiang, Haiyue
Abstract : Abstract: Bmp5 mutation can lead to microtia in mice models; however, its underlying mechanism is unclear. We analyzed circular RNA (circRNA) expression changes and associated gene regulation during embryonic development of the mouse's external ear after a point mutation occurred naturally in the BMP5 gene. The outer ear tissues of BMP5 short-eared mouse model embryos at embryonic day (E) 15.5 and E17.5 were subjected to RNA sequencing. Changes in the circRNA expression profile were detected using find_circ and the CiRi2 software. Differentially expressed circRNAs were annotated by Gene Ontology and Kyoto Encyclopedia of Genes and Genomes enrichment analyses. The circRNA expression profile differed between wild-type and mutant mouse embryos. At E15.5, differentially expressed RNAs were involved in the Hippo signaling pathway, whereas those at E17.5 were associated with stem cell pluripotency. Therefore, circRNA is involved in regulating embryonic external ear development, thus providing a basis for studying the biological aspect of its regulation.